ANTICANCER CONSTITUENTS AND CYTOTOXIC ACTIVITY OF METHANOL-WATER EXTRACT OF POLYGONUM BISTORTA L. - Intisar, Azeem; Zhang, Lingyi; Luo, Huiyang; Kiazolu, Boima; Zhang, Runsheng; Zhang, Weibing (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study was specifically designed to identify anticancer constituents in methanol-water extract of Polygonum bistorta L. and evaluate its cytotoxicity. For this purpose methanol-water (40:60 v/v) extract was subjected to conventional preparative high pressure liquid chromatography and 13 fractions were obtained. Constituents of obtained fractions were separated and identified with the help of GC-MS and LC-DAD-ESI-MS. Anticancer phenolic compounds such as gallic acid, protocatechuic acid, p-hydroxybenzoic acid, chlorogenic acid, vanillic acid, syringic acid, catechol, 4-methyl catechol, syringol and pyrogallol and fatty acids such as linoleic acid, myristic acid and palmitic acid were separated from different fractions. Fractions were evaluated for their cytotoxic activity on a rarely studied human hepatocellular carcinoma cell line (HCCLM3). 11 fractions showed good to strong cytotoxicity in a range of 200 µg/mL-800 µg/mL, whereas 2 fractions did not show any activity even at 800 µg/mL and no anticancer constituent was detected from them. 50 percent growth inhibition (GI50) values for five most active fractions were calculated and results were in a range of 86.5 (±3) µg/mL-126.8 (±3) µg/mL. 3 out of these 5 most active fractions were found to contain phenolic content in them whereas all other fractions containing phenolic content did possess cytotoxic activity that may suggest the importance of phenolic constituents in anticancer activity. Moreover, the results also showed a definite dose dependent relationship between amount of fractions and cytotoxic activity.